Fluoride prophylaxis - poison or simple way to get rid of early childhood caries (ECC) - review - Justyna Molczyk-Sieńczak; Rafał Gorzyński; Justyna Kurek; Anna Gadomska; Michał Garstka; Hanna Dominik; Zuzanna Czudy; Wojciech Pawęska; Jan Radwański; Marika Polatowska (Kazimierz Wielki University, 2023)
Introduction: As a prevention, fluoride is used systemically as well as topically in the oral cavity.  Thanks to fluoride prophylaxis, one of the most common bacterial disease in the world can be significantly reduced. This disease is dental caries. As such, it constitutes a huge problem in current stomatology, especially the type that affects small children - early childhood caries (ECC). Fluoride has beneficial effects not only in caries prevention but also in arresting and inhibiting the active decay process. Nevertheless, in recent years the use of fluoride is claimed to be controversial due to its toxic properties. Aim: The aim of this study is to summarize the current knowledge on the effect that fluoride has on caries diseases affecting children and the safety of its use based on the available research. Materials and methods: Review of the current literature based on data available in: Pubmed, Ncbi, NIH, AAPD (American Academy of Pediatric Dentistry) and EAPD (European Academy of Pediatric Dentistry) websites using the following phrases: fluoride, fluoride in caries prevention, fluoride in caries, fluoride mechanism, fluoride toxicity, fluoride safety, caries, early childhood caries (ECC). Conclusions: The use of fluoride is debatable, due to its toxic properties when used in excessive doses. The analysis of the studies proved that fluoride concentrations used in dentistry for the prevention and treatment of early childhood caries (ECC) are safe for the children's organism. The benefits resulting from its use in modern dentistry, which should be based on prophylaxis, are indisputable.